2022
DOI: 10.3390/ijerph19073807
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus-Related Health Literacy: A Cross-Sectional Study during the COVID-19 Pandemic in Italy

Abstract: The COVID-19 pandemic has caused an overabundance of valid and invalid information to spread rapidly via traditional media as well as by internet and digital communication. Health literacy (HL) is the ability to access, understand, appraise, and apply health information, making it fundamental for finding, interpreting, and correctly using COVID-19 information. A cross-sectional study of a sample of 3500 participants representative of the Italian adult population aged 18+ years was conducted in Italy in 2021. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…This instrument was used to assess levels of VL in the general Portuguese population 61 together with other questions about digital and navigational HL, and to identify the determinants of VL of the Italian population through two online and telephone surveys, performed before 15 and during the COVID-19 pandemic. 78 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This instrument was used to assess levels of VL in the general Portuguese population 61 together with other questions about digital and navigational HL, and to identify the determinants of VL of the Italian population through two online and telephone surveys, performed before 15 and during the COVID-19 pandemic. 78 …”
Section: Resultsmentioning
confidence: 99%
“…As mentioned, in some studies an updated version of the European Health Literacy Questionnaire (HLS19-Q47) was used, developed in the framework of the M-POHL collaboration (WHO Action Network on Measuring Population and Organizational Health Literacy), 100 also including four vaccination-related questions to assess the vaccination-specific HL. 15 , 78 In other surveys, participants’ HL was measured using the 12-item short version of HLS-EU-Q, integrated with three vaccine-related items extracted from the full version of HLS-EU-Q, to assess vaccine literacy among people with different levels of perceived stress related to the pandemic. As expected, people with higher HL showed lower vaccine hesitancy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is vital to understand online health information-seeking behaviours and DHL among university students in Ghana during the COVID-19 pandemic. To date, research about university students' internet surfing behaviours and COVID-19 DHL in Ghana is lacking compared to Europe [7,10,11,15,24], the USA [9], and Asia [4,12,16,18]. Besides, due to cultural, contextual, and/or geographical disparities as well as population characteristics, the findings may not be applicable in the Ghanaian context.…”
Section: Introductionmentioning
confidence: 95%
“…Some researchers reported that adolescents and young adults in schools experienced challenges in surfing the internet for COVID-19-related information [4,7,10,11,15,24]. However, these students may have had limited searching skills or problems with literacy and other issues that may have made it difficult for them to locate and understand authoritative information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation